Perceived Barriers to Weight loss Programs for Overweight or Obese Women - Nasrin Sharifi; Reza Mahdavi; Mehrangiz Ebrahimi-Mameghani (Tabriz University of Medical Sciences, 2013)
Background: In order to develop appropriate obesity control and treat¬ment strategies, the key point is to understand the barriers perceived by overweight or obese people in trying to follow weight-loss programs. This study examined perceived barriers to weight-loss programs among over¬weight or obese women.Methods: In this descriptive-analytical study, 204 overweight or obese women aged 31.97± 10.62 yr, were selected randomly from the nutritional counseling centers in 2008 in Tabriz, Iran. The mean BMI was 33.83 ±5.75 kg/ m2. A structured questionnaire including questions on barriers to weight-loss diet and physical activity was filled out for each participant by face-to-face interview. Height and weight measured objectively and demo¬graphic details were obtained. Data analysis carried out using mul¬tiple re¬gression and factor analysis.Results: The most important perceived barriers to weight-loss diets were 'situational barriers', stress, depression, and food craving. High educational level was independent determinant of situational barriers (β=0.329, P=0.048). Employee women had a higher mean score on stress and de¬pres¬sion than students and housewives. Lack of time and exercising lonely were the most important items of "External barriers" and Lack of motiva¬tion was the most important item of "internal barriers" to physical activity. Employ¬ment and being student were highly associated with external bar¬riers (β=1.018, P<0.001 and β=0.541, P= 0.002). Moreover, older women who had low educational level, perceived more internal barriers. Conclusion: Weight reducing strategies should take into account the spe¬cific perceived barriers to weight-loss diets faced by overweight or obese women, particularly situational barriers, stress and depression and food craving; and lack of time and lack of motivation as barriers to physical ac¬tivity.